KESEHATAN SEKSUAL DAN REPRODUKSI SERTA FASILITAS KESEHATAN DI LOKASI PROSTITUSI: COMMUNITY BASED PARTICIPATORY RESEARCH DENGAN PHOTOVOICE PADA PEKERJA SEKSUAL DI GUNUNG LAWU, BALI - Lestari, Made Diah; Sulistiowati, Ni Made Dian; Natalya, Ni Putu (Faculty of Psychology, Diponegoro University, 2016)
Sex workers are victims of prostitution because prostitution endangers their physical, social, and psychological health; therefore, a movement/action that empowers the community in protecting the physical, social, and psychological health of sex workers is needed. This study tries to see the views of sex workers on reproductive health and the support of health facilities in their community. The research subjects were female sex workers who work within the scope of localization (complexes) in Bali. The research approach used was a community - based participatory research (CBPR) using the photovoice method as a media to answer the research questions. Participants were 11 sex workers and social workers in Gunung Lawu. The data were analyzed using a participatory analysis and coding system. The results show stigma and discrimination were still exsist. Reproductive health is important for sex workers, but they realize that the control of their health conditions is on the external side namely the customers, pimps, and the availability of health facilities in their environment. Unfortunately, health facilities are also still limited.